2022
DOI: 10.3390/electronics11050807
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Microstrip Bandpass Filter with Two Concurrently Tuned Transmission Zeros

Abstract: In this paper, an electrically small tunable microstrip bandpass filter with two concurrently tuned transmission zeros (TZs) is presented. The filter consists of two coupled resonators and varactors as tuning elements. An application of a multipath coupling network results in TZs on both sides of the passband. The filter controlled by a single voltage has a wide tuning range from 370 MHz to 800 MHz and a low insertion loss ranging from 1.9 dB to 3.4 dB. To achieve high attenuation in the stopband, two sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Increasing the number of resonators improves the steepness of slopes in the transition bands at the expense of a higher in-band insertion loss (IL) [2,3]. For this reason, most planar filters presented in the literature are built of no more than four resonators [2,[4][5][6][7][8][9][10][11][12][13]. It is observed that the in-band IL of the inductively coupled tuned microstrip bandpass filters decreases with increasing center frequency [2,5,7,9,10,14].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing the number of resonators improves the steepness of slopes in the transition bands at the expense of a higher in-band insertion loss (IL) [2,3]. For this reason, most planar filters presented in the literature are built of no more than four resonators [2,[4][5][6][7][8][9][10][11][12][13]. It is observed that the in-band IL of the inductively coupled tuned microstrip bandpass filters decreases with increasing center frequency [2,5,7,9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The steepness of the slopes could be improved by using additional transmission zeros (TZs) spaced in the transition bands of the filter response [2,[4][5][6][7][8][9][10]12,13]. To improve the shape factor in tunable filters, the TZs should be allocated in both the lower and upper transition bands and tuned concurrently with the operating frequency.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations